"I'll wait for him": Understanding when female shoppers prefer working with gay male sales associates. (May 2017) - Rosenbaum, Mark S.; Russell, Eric M.; Russell-Bennett, Rebekah
Abstract: This article explores an under-researched area in retailing; namely, straight female shoppers' preferences for working with gay male sales associates. Study 1 employs qualitative methodology to show that female shoppers often prefer working with gay male sales associates when they are older or heavier than female sales associates. Study 2 employs experimental methodology to show that female shoppers desire to work with gay male associates more than their straight male counterparts when they are purchasing merchandise requiring non-sexual intimacy, such as apparel and cosmetics. The results should help retailers understand why many female shoppers willingly, and comfortably, work with gay male sales associates and the role of gay associates in various retail departments.